Motivation and Technological Innovation: Mapping the Digital Business Competitiveness in Lampung Province - Isnandar Agus; Irvan Patuan Marsahala Simamora; Teta Puti Sugesti; Hesti Ayuningtiyas (Goodwood, 2025)
Purpose: This study explores the link between technological innovation and the competitive advantage of household enterprises in Lampung Province (2024), specifically examining whether digital adoption facilitates business scaling. Methodology: Utilizing a qualitative descriptive framework, this study evaluates the spread of digital tools against competitiveness benchmarks, using firm characteristics and labor dynamics as control variables. Results: The analysis reveals a